Effect of Fireworks, Chinese New Year and the COVID-19 Lockdown on Air Pollution and Public Attitudes - Peter Brimblecombe; Yonghang Lai (Aerosol and Air Quality Research, 2020)
Abstract Concentrations of primary air pollutants are driven by emissions and weather patterns, which control their production and dispersion. The early months of the year see the celebratory use of fireworks, a week-long public holiday in China, but in 2020 overlapped in Hubei Province with lockdowns, some of > 70 days duration. The urban lockdowns enforced to mitigate the COVID-19 pandemic give a chance to explore the effect of rapid changes in societal activities on air pollution, with a public willing to leave views on social media and show a continuing concern about the return of pollution problems after COVID-19 restrictions are lifted. Fireworks typically give rise to sharp peaks in PM2.5 concentrations, though the magnitude of these peaks in both Wuhan and Beijing has decreased under tighter regulation in recent years, along with general reductions in pollutant emissions. Firework smoke is now most evident in smaller outlying cities and towns. The holiday effect, a reduction in pollutant concentrations when normal work activities are curtailed, is only apparent for NO2 in the holiday week in Wuhan (2015−2020), but not Beijing. Lockdown in Wuhan was characterised by decreases in NO2, along with more subtle changes in particulate matter and other pollutants. Ozone noticeably increases as there is less NO available for titration, but such change may not be widespread geographically. Beijing, where restrictions were less stringent, showed some improvement in air quality, though this is more difficult to detect, even within the 5th Ring Road.